Cloning And Promoter Analysis Of Human Choline Kinase Isoforms - Yee, Yoke Hiang (2012)
Choline kinase (CK) is the first enzyme in the CDP-choline pathway for the synthesis of phosphatidylcholine in all animal tissues. CK phosphorylates choline into phosphocholine in the presence of ATP and Mg2+. Kolina kinase (CK) merupakan enzim pertama di dalam laluan CDP-kolina untuk biosintesis fosfatidilkolina dalam semua tisu haiwan. CK memfosforilasikan kolina kepada fosfokolina dengan kehadiran ATP dan Mg2+.